METHODOLOGY FOR USING EDUCATIONAL TECHNOLOGIES TO DEVELOP CREATIVE THINKING OF TEACHERS IN THE PROFESSIONAL DEVELOPMENT SYSTEM - Dilobar Hamzayevna, Ilmurodova (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the role of educational technologies in fostering creative thinking among teachers within the professional development system, emphasizing their impact on enhancing professional skills and ensuring the continuous improvement of educational quality. Method: The research utilizes a mixed-method approach, combining qualitative interviews with educational professionals and quantitative surveys to assess the integration of various educational technologies in teacher training programs. Data were collected from a diverse group of educators engaged in ongoing professional development. Results: Findings indicate that the effective use of educational technologies significantly contributes to the development of creative thinking, with educators reporting enhanced problem-solving abilities, innovation in instructional practices, and a more dynamic approach to student engagement. Additionally, continuous exposure to modern tools fosters lifelong learning and adaptability among teachers. Novelty: The study provides a novel insight into the intersection of technology and creative pedagogical development, offering a framework for integrating technological tools into professional development programs that not only update teachers’ knowledge but also stimulate their creativity and instructional innovation.